A Literature Review: Flipped Classroom Model to Developing Students’ Higher Order Thinking Skills - Amanisa, Hanun Zata; Maftuh, Bunyamin (International Conference on Elementary Education, 2021)
This article aims to discuss the implementation of a flipped classroom model to develop higher-order thinking skills in elementary school students. The research method used is a literature study to describe the application of the model flipped classroom based on several experts and based on supporting reference studies. The focus of the discussion in this study is on the implementation of the model flipped classroom to improve and develop the higher-order thinking skills (HOTS) in the learning activity. A flipped classroom is a student-centered learning model to improve the quality of learning in the classroom. This model utilizes technology that provides additional support for student learning from a variety of learning media that can be accessed online outside the classroom, then in the classroom followed by discussion activities about material that students have obtained outside the classroom. Thus, flipped classrooms allow students to have more learning opportunities both online and offline and can assist in developing their higher-order thinking skills to achieve the goals in forming HOTS.